Identifikasi Pengetahuan Mahasiswa Teknik Industri Terhadap Implementasi Program MBKM dengan Pendekatan Analytical Network Process - Nunung Nurhasanah; Budi Aribowo; Aprilia Tri Purwandari; Dicky Sumantri; Sopian Maulana; Moza Aisyah Yasmin; Raghdawulan Raghdawulan; Cut Shity (Universitas Al Azhar Indonesia, 2022)
Outcome based education is the basis of thinking for the Industrial Engineering Department Program, Al-Azhar University, Indonesia in formulating graduate profiles. Determination of the graduate profile is an important education program so that this study program tries to accommodate the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program as an alternative learning media that is beneficial for students. This study aims to identify students' knowledge of the implementation of the MBKM program. This study uses an analytical network process approach to rank 5 questions that are the focus of students' attention in implementing the MBKM program. In addition, a descriptive analysis was also conducted on the survey results based on the five priority survey questions. In general, based on the survey, it can be said that the MBKM program has its own charm for students to develop their competencies, skills, and soft skills as a provision for future graduates. In addition, students think that the MBKM program has significant benefits in improving students' abilities. This research is still limited in processing the questionnaire manually. Future research can be continued to carry out data mining on the results of an in-depth student survey. This research has the opportunity to be developed in terms of situational analysis of the MBKM program through the Soft system methodology (SSM) approach. The situational analysis carried out will produce activities that can be carried out for continuous improvement. Keywords – Analytical network process, Decision analysis, Industrial engineering department, Outcome based education, Survey